2022
DOI: 10.1021/jacs.2c08559
|View full text |Cite
|
Sign up to set email alerts
|

A Zintl Cluster for Transition Metal-Free Catalysis: C═O Bond Reductions

Abstract: The first fully characterized boron-functionalized heptaphosphide Zintl cluster, [(BBN)P7]2– ([1]2–), is synthesized by dehydrocoupling [HP7]2–. Dehydrocoupling is a previously unprecedented reaction pathway to functionalize Zintl clusters. [Na(18-c-6)]2[1] was employed as a transition metal-free catalyst for the hydroboration of aldehydes and ketones. Moreover, the greenhouse gas carbon dioxide (CO2) was efficiently and selectively reduced to methoxyborane. This work represents the first examples of Zintl cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…16,32,33 Very recently, we have reported on the first transition-metal free Zintl catalysis with a boron-functionalized [P 7 ] cluster, which was also found to be noninnocent in the transformation. 34 Here we tether boranes to a heptaphosphane cluster and use them in Lewis acid catalysis (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,32,33 Very recently, we have reported on the first transition-metal free Zintl catalysis with a boron-functionalized [P 7 ] cluster, which was also found to be noninnocent in the transformation. 34 Here we tether boranes to a heptaphosphane cluster and use them in Lewis acid catalysis (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…16,32,33 Very recently, we have reported on the first transition-metal free Zintl catalysis with a boron-functionalized [P 7 ] cluster, which was also found to be noninnocent in the transformation. 34…”
Section: Introductionmentioning
confidence: 99%
“…Further, in our previous stoichiometric studies between [Na(18-c-6)] 2 [1] and HBpin there was no evidence of HBBN formation. 34 Therefore, we do not expect 2b′ to formed after catalysis.…”
Section: Mechanistic Investigationsmentioning
confidence: 87%
“…17,18 Recently, we have found that boron-functionalized [P 7 ] cages can be applied as transition-metal free catalysts in hydroboration reactions. 19,20 Heteroallene insertion between labile non-cluster tetrelpnictogen bonds has previously been reported. [21][22][23][24][25][26] In 2022 we found for the first time this reactivity with Zintl-derived clusters.…”
Section: Introductionmentioning
confidence: 91%
“…17,18 Recently, we have found that boron-functionalized [P 7 ] cages can be applied as transition-metal free catalysts in hydroboration reactions. 19,20…”
Section: Introductionmentioning
confidence: 99%